River water quality monitoring using statistical process control in Dungun River Basin, Terengganu, Malaysia - Tengku Nurul Aimi Balqis Tengku Malim Busu; Nor Aishah Ahad (Penerbit Universiti Kebangsaan Malaysia, 2021)
Water pollution keeps rising due to the industrialisation and urbanisation in Malaysia. This matter needs to be given serious attention to avoid further contamination of the river water. Therefore, the quality of river water should be measured to avoid water pollution. This study was carried out to determine river water quality whether the water is safe for aquatic life or not at Dungun River Basin, Terengganu, based on the chemical parameters, which are the pH value and the Total Dissolved Solids (TDS). The water sampling was conducted at three separate sites along the river, and the distance between each station is approximately 2 km. Box plot, scatter plot, and control chart are being used in the analysis. The box plot results show that the water pH value and TDS level are normally distributed with no outliers. The scatter plot shows that the pH value and TDS level have a weak positive relationship with the correlation value of 0.4063. The control chart shows the pH value and TDS level are stable and within control. However, apart from the physical, chemical, and microbiological parameters, water quality must be accessed to ensure a high quality of drinking water. Based on the National Water Quality Standard (NWQS), the result shows that pH was classified as Class IV, while TDS was classified as Class IIA. Therefore, the river water required conventional treatment, but it still can be used for irrigation.